Bird species richness, composition and abundance in pastures are affected by vegetation structure and distance from natural habitats: a single tree in pastures matters. (3rd April 2018) - Godoi, Mauricio Neves; Laps, Rudi Ricardo; Ribeiro, Danilo Bandini; Aoki, Camila; de Souza, Franco Leandro
ABSTRACT: Throughout the world, natural habitats have been replaced by pastures. Thus, bird conservation requires making pastures more accessible for birds. The use of pastures by birds inhabiting the surrounding natural habitats may be affected by the structure of pastures and their distance from natural habitats. In this study we tested whether bird species richness, composition and abundance in pastures of the Brazilian Cerrado are linked to habitat and dietary requirements and affected by vegetation structure and the distance to natural habitats. We found that pastures with more trees and shrubs had greater richness of forest birds, forest insectivorous birds and semi-forest insectivorous-frugivorous birds. Pastures with taller trees had greater richness of semi-forest insectivorous birds, and pastures closer to natural habitats had greater richness of forest frugivorous birds. Bird composition in pastures changed according to vegetation structure and distance from natural habitats, and the abundance of some bird species was positively correlated to vegetation structure and negatively correlated to distance from natural habitats. These findings highlight the importance of trees and shrubs in pastures and maintaining patches of natural habitats near pastures. Management measures can make pastures more accessible for birds from surrounding natural environments and could help in bird conservation.